2019
DOI: 10.2147/dddt.s198950
|View full text |Cite
|
Sign up to set email alerts
|

<p>Quizartinib (AC220): a promising option for acute myeloid leukemia</p>

Abstract: Quizartinib is an effective therapy for patients with FLT3-ITD acute myeloid leukemia (AML) by continuing to inhibit the activity of FLT3 gene, leading to apoptosis of tumor cells. Multiple clinical trials have proved that it is effective in relapsed or refractory AML with an FLT3-ITD mutation. In this review, we focus on the characteristics of FLT3/ITD mutations, the mechanism and pharmacokinetics of quizartinib, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 61 publications
0
41
0
3
Order By: Relevance
“…Several FLT3 inhibitors have been evaluated in clinical trials of patients with AML 56 . Among these, the second-generation FLT3 inhibitors quizartinib and gilteritinib as single agents improved marrow remission rates and OS compared with traditional salvage chemotherapies (investigator’s choice of high-intensity therapies such as fludarabine–Ara-C–granulocyte colony-stimulating factor–idarubicin or mitoxantrone-etoposide-cytarabine, or low-intensity therapies such as HMAs or LDAC) in relapsed/refractory FLT3 -mutated AML patients 57 60 . Midostaurin is used in combination with induction chemotherapy for the first-line treatment of patients with FLT3- ITD– or FLT3- TKD–mutated AML 61 .…”
Section: The Evolving Role Of Hybrid Regimens Co-targeting Bcl-2 and mentioning
confidence: 99%
“…Several FLT3 inhibitors have been evaluated in clinical trials of patients with AML 56 . Among these, the second-generation FLT3 inhibitors quizartinib and gilteritinib as single agents improved marrow remission rates and OS compared with traditional salvage chemotherapies (investigator’s choice of high-intensity therapies such as fludarabine–Ara-C–granulocyte colony-stimulating factor–idarubicin or mitoxantrone-etoposide-cytarabine, or low-intensity therapies such as HMAs or LDAC) in relapsed/refractory FLT3 -mutated AML patients 57 60 . Midostaurin is used in combination with induction chemotherapy for the first-line treatment of patients with FLT3- ITD– or FLT3- TKD–mutated AML 61 .…”
Section: The Evolving Role Of Hybrid Regimens Co-targeting Bcl-2 and mentioning
confidence: 99%
“…Targeting mutant FLT3 by small molecule inhibitors has rapidly emerged as a new therapeutic approach in patients with AML. Different FLT3 inhibitor therapeutic agents have been developed and are summarized in Tables 1, 2 [9,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Flt3mentioning
confidence: 99%
“…[37] EFS and OS at 2 years were 39% and 34% in younger and 53% and 46% in older patients, respectively [38] Recommended as front line therapy for AML with FLT3-ITD and FLT3-TKD [9,39] Sunitinib Some promising results in phase I/II clinical trials, but with high incidence of adverse effects [40,41] Gilteritinib a R/R FLT3-mutated AML, median OS for single agent gilteritinib was significantly longer than chemotherapy (9.3 months vs. 5.6 months). Median EFS was 2.8 months in the gilteritinib group and 0.7 months in chemotherapy group [42] Recommended as new standard therapy for R/R FLT3-mutated AML [43] Lestaurtinib Failed to demonstrate any overall clinical benefit in a phase III trial when combined with intensive chemotherapy in patients with newly diagnosed FLT3-ITD-mutated AML [9,44,45] Crenolanib a Combine with 7 + 3 regimen can overcome the poor prognostic implication of adverse mutations co-occurring with mutated FLT3 [46] Incorporation of crenolanib into frontline intensive chemotherapy resulted high ORR and may replace Midostaurin in the upfront setting [47] Type 2 Quizartinib a Showed efficacy in multiple clinical trials in R/R AML with FLT3-ITD mutation [48][49][50] Recommended for patients with rapidly proliferative disease and very poor prognosis [51] Sorafenib Combine with intensive chemotherapy improves OS in newly diagnosed, FLT3-ITD mutated AML regardless allogeneic HSCT [52] Improved OS for FLT3-ITD AML relapsing after allo-HSCT […”
Section: Cebpamentioning
confidence: 99%
“…The results showed that the expression of E-cadherin was upregulated, and the expression of N-cadherin, Vimentin, and Slug was downregulated, demonstrating that the EMT pathway was blocked in cervical cancer cells after GLP treatment. The JAK/STAT5 signaling pathway is involved in numerous important biological processes including cell proliferation, differentiation, apoptosis, and immune regulation [29]. Data from Giordano et al [30] illustrated that the changes of the JAK/STAT5 signaling pathways in colorectal cancer can improve the therapeutic effects mediated by LY6G6D.…”
Section: Discussionmentioning
confidence: 99%